Uptake, biotransformation and elimination of selected pharmaceuticals in a freshwater invertebrate measured using liquid chromatography tandem mass spectrometry. (September 2017) - Miller, Thomas H.; Bury, Nicolas R.; Owen, Stewart F.; Barron, Leon P.
Abstract: Methods were developed to assess uptake and elimination kinetics in Gammarus pulex of nine pharmaceuticals (sulfamethazine, carbamazepine, diazepam, temazepam, trimethoprim, warfarin, metoprolol, nifedipine and propranolol) using targeted LC-MS/MS to determine bioconcentration factors (BCFs) using a 96 h toxicokinetic exposure and depuration period. The derived BCFs for these pharmaceuticals did not trigger any regulatory thresholds and ranged from 0 to 73 L kg −1 (sulfamethazine showed no bioconcentration). Metabolism of chemicals can affect accurate BCF determination through parameterisation of the kinetic models. The added selectivity of LC-MS/MS allowed us to develop confirmatory methods to monitor the biotransformation of propranolol, carbamazepine and diazepam in G. pulex . Varying concentrations of the biotransformed products; 4-hydroxypropranolol sulphate, carbamazepine-10, 11-epoxide, nordiazepam, oxazepam and temazepam were measured following exposure of the precursor compounds. For diazepam, the biotransformation product nordiazepam was present at higher concentrations than the parent compound at 94 ng g −1 dw. Overall, the results indicate that pharmaceutical accumulation is low in these freshwater amphipods, which can potentially be explained by the rapid biotransformation and excretion. Graphical abstract: Highlights: Bioconcentration factors of 9 pharmaceuticals in G. pulex ranged from 0 to 73 L kg −1 G. pulex are capable of pharmaceutical biotransformation. Five pharmaceutical metabolites were determined up to 94.5 ng g −1 Biotransformation can affect BCFtotal estimates if metabolites are not accounted for.